Estudio Descriptivo De La Autonomía Motivacional En El Alumnado De Educación Secundaria De La Provincia De Benguela (Angola) - Ferreira, José Francisco; Reche, María Pilar Cáceres; Cabrera, Arturo Fuentes (European Scientific Journal, ESJ, 2017)
The study of motivation has a very important role in understanding of school success. The teachers and the education of parents and tutors are the key elements that influence the motivational dynamics for student learning, which is a crucial aspect to self-regulate the learning process in a positive way. This research aims to analyze the influence of the school context on the development of the motivational autonomy of Secondary Education students in the municipality of Baía Farta, Benguela province, Angola. For this purpose, a quantitative descriptive methodology was developed through a Likert scale questionnaire administered to teachers and students. The total sample of the study consisted of 650 students (60.1% men and 39.9% women) and 72 teachers (54.2% men and 45.8% women). The main results point to the commitment and active participation of students through motivational strategies that are implemented through the activities planned by the school. Creating a supportive environment for the student to be motivated requires the development of a role of the guiding teacher, guide and support in the teaching and learning process, as opposed to a traditional conception of teaching more closed and hierarchical.